Online Shopping as Cultural Disorientation during Covid-19 Pandemic for Women Community Leaders and Cadre in Village: Systemic Functional Linguistics Approach - Chalimah Chalimah; Susi Darihastining; Ama Noor Fikrati (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Research basis in finding out whether there is cultural disorientation during Covid-19 Pandemic that happen to women community leaders and cadre in a village ‘Banjaragung Jombang’. Case study with systemic functional linguistic approach: transitivity is used in this research. Findings show that there is cultural disorientation in doing online shopping seen in aspects of salience, mood, conflict, and relapse. The women community leaders and cadre tend to think that online shopping is essential, enjoyable and easy but they tend to have self motivation to keep doing online shopping and get trouble in economy and time consuming which gives impact in their work. The novelty of this research is that the social case can be investigated through linguistics.